2018
DOI: 10.2196/preprints.10807
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Acute HIV Infection in Youth: Protocol for the Adolescent Trials Network 147 (ATN147) Comprehensive Adolescent Research and Engagement Studies (CARES) Study (Preprint)

Abstract: Background: Early treatment studies have shown that prompt treatment of HIV with

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…We anticipate a higher proportion of women in our sample from New Orleans and that while most youth from New Orleans will be African American, youth in Los Angeles will also be Latino and White and predominately GBTY. Further details on each of the ATN CARES studies may be found in the corresponding study protocol papers [112,[115][116][117][118]. Recruitment Process.…”
Section: Peer Support Via Social Mediamentioning
confidence: 99%
“…We anticipate a higher proportion of women in our sample from New Orleans and that while most youth from New Orleans will be African American, youth in Los Angeles will also be Latino and White and predominately GBTY. Further details on each of the ATN CARES studies may be found in the corresponding study protocol papers [112,[115][116][117][118]. Recruitment Process.…”
Section: Peer Support Via Social Mediamentioning
confidence: 99%
“…We hypothesize that by providing rapid STI testing among high-risk adolescent populations, we will find a high prevalence of STIs. We also expect that by providing same-day testing results, we will be able to [20][21][22][23][24].…”
Section: Objectivesmentioning
confidence: 99%